NEW ECONOMIC WORDS IN UZBEK AND KARAKALPAK LANGUAGES - Nurmanova Salomat Tursinbayevna (Galaxy International Interdisciplinary Research Journal, 2023)
The article discusses new words and terms related to the economy in the Uzbek and Karakalpak languages.